Coach-trainee communication as basis for adolescent deviant behavior control - Rodermel, T. A.; Shamukhametova, E. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to rate and analyze the coaches' communicative skills in the adolescent deviant behavior control context and offer the adolescent deviant behavior control recommendations for the training and competitive service.